Efektivitas Metode RGEC Dalam Menilai Penerapan Green Banking Pada Bank Swasta Di Indonesia - Wahyudi, Henri (Universitas Muhammadiyah Surakarta, 2025)
This study examines the extent to which Indonesian national private banks are implementing the green banking program. A descriptive research method with a quantitative approach was employed to assess the health level of conventional banks (Bank BCA and Bank Bukopin) and Sharia banks (Bank BCA Syariah and Bank BTPN syariah) from 2021 to 2023 using the RGEC method. The findings indicate that Bank BCA is in a state of robust financial health, whereas Bank Bukopin is exhibiting signs of financial distress with respect to its risk profile. Similarly, Bank BCA Syariah is in a healthy condition, whereas Bank BTPN Syariah is in an unhealthy condition. All banks have implemented the principles of good corporate governance. With regard to profitability, Bank BCA is in an optimal position, whereas Bank BCA Syariah is experiencing suboptimal performance. Conversely, the levels of health observed in Bank Bukopin and Bank BTPN Syariah are, respectively, unhealthy and very healthy. The study additionally reveals that both conventional and Islamic banks demonstrate exemplary managerial performance. In conclusion, the study finds that Indonesian national private banks are in a healthy state and thus suitable for implementing the Green Banking program.